The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12974-022-02515-w
|View full text |Cite
|
Sign up to set email alerts
|

Early-life stress elicits peripheral and brain immune activation differently in wild type and 5xFAD mice in a sex-specific manner

Abstract: Background The risk of developing Alzheimer’s disease (AD) is modulated by genetic and environmental factors. Early-life stress (ELS) exposure during critical periods of brain development can impact later brain function and health, including increasing the risk of developing AD. Microglial dysfunction and neuroinflammation have been implicated as playing a role in AD pathology and may be modulated by ELS. To complicate matters further, sex-specific effects have been noted in response to ELS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 60 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…Brain development is strongly influenced by external factors and early life experiences ( Hensch, 2004 ; Miguel et al, 2019 ). Here, we used ELS, an established model to interfere with early brain development with long-lasting consequences for psychopathological risks later in life ( Teicher et al, 2016 ; Joëls et al, 2018 ; Bachiller et al, 2022 ; Catale et al, 2022 ). We used SClm to detect possible alterations in chloride maturation in the mPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Brain development is strongly influenced by external factors and early life experiences ( Hensch, 2004 ; Miguel et al, 2019 ). Here, we used ELS, an established model to interfere with early brain development with long-lasting consequences for psychopathological risks later in life ( Teicher et al, 2016 ; Joëls et al, 2018 ; Bachiller et al, 2022 ; Catale et al, 2022 ). We used SClm to detect possible alterations in chloride maturation in the mPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Brain development is strongly influenced by external factors and early life experiences (Hensch, 2004; Miguel et al, 2019). Here we used ELS, an established model to interfere with early brain development with long-lasting consequences for psychopathological risks later in life (Bachiller et al, 2022; Catale et al, 2022; Joёls et al, 2018; Teicher et al, 2016). We used SClm to detect possible alterations in chloride maturation in the mPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, this balance shifts to the opposite pattern by puberty, such that adolescent and adult females have more “activated” microglia in the same brain regions (Schwarz et al, 2012 ). In the context of ELA, work by Bachiller et al ( 2022 ) discovered that the extent of Iba1+ staining coverage is increased in the hippocampus of MS male, but not female, mice at P15. However, the same study found an increase in the percentage of microglia with an “activated” morphology in the PFC of MS females in comparison to male counterparts (Bachiller et al, 2022 ).…”
Section: Emerging Microglia-dependent Mechanismsmentioning
confidence: 99%
“…In the context of ELA, work by Bachiller et al ( 2022 ) discovered that the extent of Iba1+ staining coverage is increased in the hippocampus of MS male, but not female, mice at P15. However, the same study found an increase in the percentage of microglia with an “activated” morphology in the PFC of MS females in comparison to male counterparts (Bachiller et al, 2022 ). Thus, it is possible that experiencing adversity during a developmental period in which microglia show sex differences in number and morphology in certain brain regions could impact males and females differently, thereby resulting in sex-specific and region-specific ELA-induced changes in synaptic pruning and ultimately divergent behavioral outcomes.…”
Section: Emerging Microglia-dependent Mechanismsmentioning
confidence: 99%